2022
DOI: 10.1002/anie.202114471
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Transient Supramolecular Chiral G‐quadruplex Hydrogels by a Chemically Fueled Non‐equilibrium Self‐Assembly Strategy

Abstract: The temporal and spatial control of natural systems has aroused great interest for the creation of synthetic mimics. By using boronic ester based dynamic covalent chemistry and coupling it with an internal pH feedback system, we have developed a new chemically fueled reaction network for non‐equilibrium supramolecular chiral G‐quadruplex hydrogels with programmable lifetimes from minutes, to hours, to days, as well as high transparency and conductivity, excellent injectability, and rapid self‐healing propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…Li and coworkers proposed that the transient G-quadruplex hydrogels with a tunable lifetime could provide attractive potentials for next-generation smart applications due to the rapid self-healability and injectability. 50 The application in fluid confinements and transient electronics of the resultant transient hydrogels in our study confirmed the potential. Our experimental results, along with the existing literature, led us to provide a new approach for the design of next generation intelligent materials with self-adaptability and interactivity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Li and coworkers proposed that the transient G-quadruplex hydrogels with a tunable lifetime could provide attractive potentials for next-generation smart applications due to the rapid self-healability and injectability. 50 The application in fluid confinements and transient electronics of the resultant transient hydrogels in our study confirmed the potential. Our experimental results, along with the existing literature, led us to provide a new approach for the design of next generation intelligent materials with self-adaptability and interactivity.…”
Section: Discussionsupporting
confidence: 77%
“…Until recently, Li and coworkers developed the first transient supramolecular chiral G-quadruplex hydrogel with a tunable lifespan ranging from minutes to hours. 50 They found that the dynamic formation and dissociation of the borate eater bond between guanosine and 5-fluorobenoxane driven by chemical fuels (KOH and 1,3-propanesultone) led to a precipitate-solution-gel-precipitate transition. Our similar finding, the dynamic precipitate-to-gel-to-precipitate transition mediated by fuel-driven and enzyme-regulated co-assembly of GMP, La 3+ , and urease, confirmed that observation.…”
Section: Discussionmentioning
confidence: 99%
“…First, advanced assembly strategies require development to construct unique guanine analogue-based assemblies. A typical example is the construction of the programmable transient G-quadruplex hydrogel, which is expected to be next-generation adaptive and an interactive smart material . Under nonequilibrium conditions, the boronic ester bond formed in situ and dissociated in KOH or lactone fuel.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…A typical example is the construction of the programmable transient G-quadruplex hydrogel, which is expected to be next-generation adaptive and an interactive smart material. 46 Under nonequilibrium conditions, the boronic ester bond formed in situ and dissociated in KOH or lactone fuel. The gel went through a cycle of precipitate− solution−gel−precipitate, which offered an optional choice for engineering smart materials.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…In the past thirty years, supramolecular chemistry has become even more sophisticated and quickly developed due to its applications in a variety of disciplines and fields [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. As a typical supramolecular material, low-molecular-weight gels (LMWGs) are a kind of soft material between a solid and liquid which have been developed rapidly and widely used in electrolyte materials [ 12 ], sensors [ 13 , 14 ], drug delivery systems [ 15 ], liquid crystal [ 16 ], supramolecular chirality [ 17 , 18 , 19 ], light-harvesting systems [ 20 , 21 ], surfactants [ 22 ] and other fields [ 23 , 24 , 25 , 26 , 27 , 28 ]. Organic molecules can be self-assembled into organogel or hydrogel under the driving force of noncovalent interactions, such as a hydrogen bond, metal coordination, π–π stacking, hydrophobic effect, electrostatic force and van der Waals force [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%